SISTEM KEKERABATAN SUKU MANDAILING DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Ibrahim, Ibrahim; Ibrahim, Bedriati; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: One of the ethnic groups in Indonesia is the Mandailing tribe. The Mandailing Tribe is a tribe originating from the South Tapanuli region. The Mandailing tribe is one of the Batak sub-ethnic groups who live along the Bukit Barisan Utara Sumater province. The Mandailing tribal community also has a custom that regulates life that is preserved for generations which makes it a way of life and has norms or rules that must be obeyed by each individual. The purpose of my research is 1) To find out the history of the Mandailing system of kinship, 2) To find out the role of the Mandailing system of kinship in the Rumbai Coastal District of Pekanbaru City. 3) To find out the norms in the kinship system of the Mandailing Tribe in the Rumbai Coastal District of Pekanbaru City. 4) To find out the shift in the kinship system of the Mandailing Tribe in the Rumbai Coastal District of Pekanbaru City. The method used is the historical method by exploring and data collection techniques through observation techniques, interview techniques, and literature study techniques. The results of this study are the shifting of tasks from the Mandailing system of kinship in the Rumbai Pesisir District, Pekanbaru City.Key Words: Kinship, Mandailing, Rumbai Pesisir